Anti-corrosion and conductive materials

By forming MgO and conductive TiO with cubic crystal structures in magnesium-titanium materials, the dual requirements of corrosion resistance and conductivity of fuel cell bipolar plates in highly corrosive environments are solved, and corrosion resistance and conductivity in acidic environments are achieved improves the stability of the material and the performance of fuel cells.

CN111403769BActive Publication Date: 2025-01-14ROBERT BOSCH GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN201911369580.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-27
Filing Date
2019-12-26
Publication Date
2025-01-14
Estimated Expiration
2039-12-26

AI Technical Summary

Technical Problem

In highly corrosive environments, metal materials such as fuel cell bipolar plates need to have both corrosion-proof and conductive properties, but the prior art is difficult to find electron transfer that can maintain corrosion resistance in an acidic environment and promote oxygen reduction reaction. Material.

Method used

TixMg1-xOy is used, where x is 0 to ≤1, y is 1 to ≤2, and contains at least 50% of the cubic crystal structures MgO and TiO, TiO is the conductive phase, MgO is the electrically insulated phase, through the oxidation of metals The alloy is formed and the oxidation degree is controlled at high temperature to form an anti-corrosion conductive layer with an interface contact resistance of less than 0.1 Ohm cm2.

Benefits of technology

It realizes the corrosion resistance and conductivity of the material in high temperature and acidic environments, reduces the corrosion risk of metal substrates, and improves the performance and life of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111403769B_ABST
    Figure CN111403769B_ABST
Patent Text Reader

Abstract

The present invention discloses an anti-corrosion and conductive material. The anti-corrosion and conductive substrate comprises a body portion and a surface portion comprising a magnesium-titanium material having formula (I): Ti x Mg 1‑x O y (I), wherein x is a number from 0 to ≤ 1, and y is a number from 1 to ≤ 2, and wherein at least about 50% of the magnesium titanium material has a cubic crystal structure, and wherein the magnesium titanium material is configured to impart corrosion protection and electrical conductivity properties to the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to corrosion resistant and electrically conductive materials, and in some embodiments to magnesium-titanium-based materials that are electrically conductive but chemically inert and can be used to impart corrosion resistant and electrically conductive properties to substrates, and methods of making the same. Background Art

[0002] Metals have been widely used materials for thousands of years. Various methods have been developed to protect metals and prevent them from corroding or decomposing into oxides, hydroxides, sulfates and other salts. In some industrial applications, metals are particularly susceptible to corrosion due to the operating environment. A non-limiting example can be the metal components of fuel cells and their bipolar plates (BPP). In addition, certain components such as BPP not only need to be chemically inert enough to resist degradation in the highly corrosive environment of fuel cells, but also need to be conductive to promote electron transfer in the oxygen reduction reaction of fuel cells. Finding materials that meet these two criteria has always been a challenge. Summary of the invention

[0003] In at least one embodiment, a corrosion resistant and conductive substrate is disclosed. The substrate may include a bulk portion. The substrate may further include a surface portion comprising a magnesium-titanium material having formula (I):

[0004] Ti x Mg 1-x O y (I),

[0005] Wherein x is a number from 0 to ≤1, and y is a number from 1 to ≤2, and wherein at least about 50% of the magnesium titanium material comprises MgO and TiO having a cubic crystal structure. The magnesium titanium material is configured to impart corrosion resistance and conductive properties to the substrate. The magnesium titanium material may include less than about 10 atomic % of Ti. The magnesium titanium material may include greater than about 10 atomic % of Ti such that the material further comprises MgO and TiO nanodomains. The TiO nanodomains may be conductive. The conductivity of the material may be greater than about 100 Scm -1 The interfacial contact resistance between the substrate and the coating (ie, the interfacial contact resistance between the bulk portion and the magnesium-titanium material) may be less than about 0.1 Ohm cm 2 The body portion may be steel. The body portion may be glass, and the material may be configured to form a transparent film on the surface portion.

[0006] In an alternative embodiment, a bipolar plate (BPP) for a proton exchange membrane fuel cell (PEMFC) is disclosed. The BPP may include a metal substrate having a bulk portion and a surface portion comprising a corrosion resistant conductive material. The material may have formula (II)

[0007] M xA 1-x O y (II),

[0008] wherein M is a transition metal or a post-transition metal, A is an alkali metal or an alkaline earth metal, x is a number from 0 to ≤ 1, and y is a number from 1 to ≤ 2. At about 80°C, at a pH of about 3, and in the presence of ~0.1 ppm HF in solution, the corrosion resistance of the coating can be less than about 10 µA cm -2 The electrical conductivity of the material may be greater than about 100 S cm -1 The material may have a cubic crystal structure of at least 50%. The body portion may include steel. M may include Ti and A may include Mg. The material may include MgO and TiO nanodomains, each nanodomain having a radius measuring about 1 to 100 nm. The TiO nanodomains may be conductive and the MgO domains are electrically insulating. The interface contact resistance between the body portion and the corrosion resistant conductive material may be less than about 0.1 Ohm cm 2 .

[0009] In yet another embodiment, a method for making a magnesium-titanium corrosion resistant and conductive material is disclosed. The method may include oxidizing Ti in a substantially oxygen-free environment. x Mg 1-x Intermetallic alloys to form Ti x Mg 1-x O y A material wherein x is a number from 0 to <1, y is a number from 1 to <2, and the ratio of Ti:Mg is less than 1:2. The method may further include oxidizing Ti x Mg 1-x O y The material is formed into a substantially chemically inert and insulating MgO region and a conductive TiO region. The magnesium-titanium corrosion resistant and conductive material may include less than about 10 atomic % Ti. The method may further include depositing Ti by electrochemical deposition. x Mg 1-x The intermetallic alloy is deposited onto a substrate. The method may include controlling the degree of oxidation by introducing (one or more) oxidizing and / or reducing agents. The method may include forming Ti at a temperature greater than about 100°C x Mg 1-x Intermetallic alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 depicts a schematic composition of a proton exchange membrane fuel cell including a bipolar plate according to one or more embodiments;

[0011] Figure 2shows a perspective view of a non-limiting example of a bipolar plate having a body portion and a surface portion including corrosion resistant and conductive material according to one or more embodiments;

[0012] Figures 3A-3E Depicted is a diagram showing the Mg disclosed herein x Ti 1-x Plots of the density functional theory (DFT) calculated electronic density of states for various compositions of the O system; and

[0013] Figure 4 The DFT-calculated convex hull plot of MgO-TiO shows various Ti x Mg 1-x O Formation energies of mixtures and their miscibility. DETAILED DESCRIPTION

[0014] Embodiments of the present disclosure are described herein. However, it is to be understood that the disclosed embodiments are merely examples, and other embodiments may take different and alternative forms. The drawings are not necessarily to scale; some features may be magnified or minimized to show the details of a particular component. Therefore, the specific structural and functional details disclosed herein should not be interpreted as restrictive, but only as a representative basis for teaching those skilled in the art to utilize the present invention in various ways. As will be understood by those of ordinary skill in the art, the various features illustrated and described with reference to any of the accompanying drawings may be combined with the features illustrated in one or more other drawings to produce an embodiment that is not explicitly illustrated or described. The combination of the illustrated features provides a representative embodiment for a typical application. However, various combinations and modifications of features consistent with the teachings of the present disclosure may be desirable for specific applications or embodiments.

[0015] Unless expressly indicated otherwise, all numerical quantities in this specification indicating dimensions or material properties are to be understood as being modified by the word "about" in describing the broadest scope of the present disclosure.

[0016] The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation herein and to general grammatical variations of the initially defined abbreviation, mutatis mutandis. Unless expressly stated to the contrary, measurements of properties are determined by the same techniques as previously or later referred to for the same property.

[0017] The terms "substantially" or "approximately" may be used herein to describe the disclosed or claimed embodiments. The terms "substantially" or "approximately" may modify a value or relative property disclosed or claimed in the present disclosure. In such cases, "substantially" or "approximately" may mean that the value or relative property it modifies is within ±0%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or 10% of the value or relative property.

[0018] The description of a group or class of materials suitable for a given purpose in conjunction with one or more embodiments of the present invention implies that mixtures of any two or more of the members of the group or class are also suitable. The description of ingredients in chemical terms refers to the ingredients when added to any combination specified in the specification, and does not necessarily exclude chemical interactions between the ingredients of the mixture once mixed. The first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation herein and to the conventional grammatical variants of the initially defined abbreviation, mutatis mutandis. Unless expressly stated to the contrary, the measured values ​​of properties are determined by the same techniques as mentioned before or after for the same property.

[0019] Metals are a class of materials used in a wide range of industries including automobiles, construction, home appliances, tools, pipes, rails, coinage, and more. Humans have used metals for thousands of years, and they are still the material of choice for certain applications due to their properties such as strength and elasticity. However, for many applications that use metals as raw materials, corrosion of metals is the main cause of fatigue and life limitations.

[0020] Corrosion is a natural process that converts refined metals into chemically more stable forms, such as oxides, hydroxides, sulfides, and / or other salts of the metal. This conversion represents a gradual destruction of the metallic material caused by electrochemical oxidation of the metal in a reaction with an oxidant, such as oxygen or sulfate. Corrosion can be caused by exposing the metal substrate to moisture in the air, solutions with a relatively low pH, various chemicals (such as acids), microorganisms, elevated temperatures, and / or other factors. Especially in acidic environments, corrosion begins at the interface between the bulk metal material (e.g., steel) and a solution (e.g., ions dissolved in water or a surface layer of water that react to degrade the bulk material).

[0021] Many efforts have been made to prevent or slow down the corrosion of metals. For example, various types of coatings have been developed. Exemplary coatings include applied coatings such as paints, platings, enamels; reactive coatings containing corrosion inhibitors such as chromates, phosphates, conductive polymers, surfactant-based chemicals designed to inhibit electrochemical reactions between the environment and the metal substrate; anodized surfaces; or biofilm coatings. Other anti-corrosion methods include controlled permeability formwork, cathodic protection, or anodic protection.

[0022] However, the most common solution to the corrosion problem is still to strengthen the vulnerable metal surface with a coating. Most corrosion-resistant surfaces thus include one or more chemically inert coatings or protective layers that can slow down and / or at least partially prevent the occurrence of corrosion. However, it remains a challenge to find materials that have significant corrosion protection properties while also being non-toxic, environmentally friendly, economical, and having excellent performance characteristics.

[0023] In addition, some applications are very susceptible to corrosion due to their environmental factors. A non-limiting example of this application is a proton exchange membrane fuel cell (PEMFC). PEMFC represents an environmentally friendly alternative to internal combustion engines for various vehicles (such as cars and buses). PEMFC generally has the characteristics of relatively high efficiency and power density. A very attractive feature of the PEMFC engine is carbon-free emissions, provided that the hydrogen fuel is obtained in an environmentally friendly manner. In addition to being a green engine, PEMFC can also be used in other applications, such as fixed power supplies and portable power supplies.

[0024] The operating environment of the PEMFC itself is prone to corrosion for a variety of reasons. For example, there is a low voltage between the start-up and shutdown of the PEMFC, the PEMFC has a strongly acidic environment, fluoride ions are released from the polymer membrane during the operation of the PEMFC, both H2 and O2 are present at the anode during the start-up and shutdown period (which leads to a high cathode potential, producing cathode corrosion), fuel permeation of hydrogen or oxygen from the anode to the cathode or from the cathode to the anode, etc. The PEMFC thus requires durable components that can withstand the above conditions.

[0025] exist Figure 1 A non-limiting example of a PEMF cell is depicted in . The core component of the PEMFC 10 is the membrane electrode assembly (MEA) 12, which helps to produce the electrochemical reaction required to separate electrons. The MEA 12 includes subcomponents such as electrodes, catalysts, and polymer electrolyte membranes. In addition to the MEA 12, the PEMFC 10 typically includes other components such as current collectors 14, gas diffusion layers 16, gaskets 18, and bipolar plates 20.

[0026] The bipolar plate or BPP 20 is implemented in the PEMFC stack to distribute gases, collect current and separate the single cells in the stack from each other. The BPP 20 also provides additional functions, such as removing reaction products and water and thermal management within the PEMFC 10. The BPP 20 thus forms a key part of the PEMFC. The BPP 20 is also a relatively expensive component and a common cause of degradation of the PEMFC system. For example, the BPP can constitute about 60-80% of the weight of the stack, about 50% of the volume of the stack, and about 25-45% of the cost of the stack. In order to keep costs low, the BPP 20 is typically made of metal, especially steel, such as stainless steel. Alternative materials such as aluminum can be used. Since metal plates are susceptible to corrosion within the PEMFC system, efforts have been made to prevent corrosion.

[0027] Furthermore, in the PEMFC 10, another material challenge is presented to the BPP 20, as the BPP 20 is also required to be conductive to facilitate electron transfer for the oxygen reduction reaction. Therefore, the BPP 20 material needs to be conductive but chemically inert to react with ions present in the PEMFC 10 environment.

[0028] Typically, the BPP metal surface contains a coating, such as a graphite-like coating or a protective oxide or nitride coating, to improve the corrosion resistance of the BPP 20. The surface of the BPP 20 may thus include elements such as Fe, Cr, Ni, Mo, Mn, Si, P, C, S, or combinations thereof. Alternative coatings include Ti alloys, doped TiO x , TiN, CrN or ZrN. However, in highly corrosive environments, such as in PEMFC 10 (where the coating is more likely to degrade faster), there is still a need for an economically viable coating that is corrosion resistant, protective against acids (such as HF) at the PEMFC operating temperature of about 80°C, electrically conductive, and at the same time capable of forming a coherent interface (i.e., low interfacial contact resistance) with the metal substrate.

[0029] The materials disclosed herein solve one or more of the above problems and / or provide the benefits identified herein. A non-limiting example of BPP 20 is shown in Figure 2 . BPP 20 represents a non-limiting example of a substrate having a solid or body portion 22 and a surface portion 24. Body portion 22 may be formed of a metal such as steel, stainless steel, aluminum, copper, alloys of two or more metals, etc. or a combination thereof. Alternatively, body portion 22 may be formed of a composite material such as a carbon-carbon composite, a carbon-polymer composite. Still alternatively, body portion 22 may be made of graphite.

[0030] The surface portion 24 comprises a corrosion resistant, chemically inert and electrically conductive material. The entire area of ​​the surface portion 24 may comprise the material. Alternatively, the surface portion 24 may include one or more sub-portions that do not contain the material. Preferably, the entire surface portion 24 comprises the material to protect the entire BPP 20 from corrosion. In other applications (such as non-BPP applications), only a small portion of the surface portion 24 may comprise the material, such as less than ½, ¼, 1 / 8, 1 / 16, 1 / 32, etc. of the surface portion may comprise the material.

[0031] The surface portion 24 may include one or more layers of the material. The material thickness on the surface portion 24 may be adjusted according to the needs of a particular application. For example, the material may form a relatively thin film so that the material forms a transparent film. Non-limiting examples of material layer thickness may be approximately 0.1 to 0.8 μm, 0.2 to 0.6 μm, or 0.3 to 0.5 μm. Alternatively, the material may be stacked to form a relatively thick deposit having a size greater than 1 μm on the surface portion 24. The material may form one or more layers or multiple layers on the body portion 22. The material may form 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or more layers on the body portion 22.

[0032] The material may be a magnesium-titanium material having formula (I)

[0033] Ti x Mg 1-x O y (I),

[0034] wherein x is a number from 0 to ≤1, and y is a number from 1 to ≤2.

[0035] Alternatively, the material may have formula (II)

[0036] M x A 1-x O y (II),

[0037] wherein M is a transition metal or a post-transition metal, A is an alkali metal or an alkaline earth metal,

[0038] wherein x is a number from 0 to ≤1, and y is a number from 1 to ≤2.

[0039] M in formula (II) can be a transition metal from Group 2B-8B. Non-limiting examples of suitable transition metals can include Zn, Cd, Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Re, Ru, Co, Rh, Ir, Ni, Zn, etc. M can also be a late transition metal from Group 3A-6A. Non-limiting examples of suitable late transition metals can include Al, Sn, Bi, etc.

[0040] The materials according to formula (I) and (II) comprise a mixture of two oxides, a first oxide having an electrically insulating, substantially chemically inert phase such as MgO and a second oxide having a conductive phase such as TiO. The insulating phase of the first oxide helps stabilize the conductive phase of the second oxide. The coating is not only conductive but also chemically inert, so that the coating does not substantially react with ions such as H in an acidic solution. + 、F - The material is thus both electrically conductive and corrosion-resistant.

[0041] The material may include less than about 10 atomic % Ti. Atomic percent refers to the percentage of an atom relative to the total number of atoms. For example, the material may include about 1 to 9.9 atomic % Ti, 2 to 8 atomic % Ti, or 3 to 7 atomic % Ti. Alternatively, the material may include about 1 to 3 atomic % Ti, 1.5 to 2.8 atomic % Ti, or 1.7 to 2.5 atomic % Ti. The material may include approximately 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5 9.4, 9.5, 9.6, 9.7, 9.8 or 9.9 atomic % Ti.

[0042] The concentration of Ti affects the structure of the material. At low concentrations of Ti, the system is Mg-rich and at least a portion of the material can form a long-range ordered phase in which both TiO and MgO have a cubic crystal structure. Low concentrations can be less than about 3 atomic % at ambient temperature or less than about 10 atomic % at elevated temperature or pressure. The low concentration can be any of the concentrations listed above below about 10 atomic % Ti, specifically about 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.8, 7.9, 8.0, 8.1 9.8, 9.9, 10.0, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0, 12.1, 12.2, 12.3, 12.4, 12.5, 12.6, 12.7, 12.8, 12.9, 13.0, 13.1, 13.2, 13.3, 13.4, 13.5, 13.6, 13.7, 13.8, 13.9, 14.1, 14.2 The material may have at least about 50, 55, 57, 60, 62, 65, 67, 70, 72, 75, 77, 80, 82, 85, 90, 92, or 95% cubic crystal structure. About 50 to 90%, 55 to 85%, or 60 to 80% of the material may have a substantially cubic crystal structure.

[0043] Ti is slightly immiscible within the cubic crystal structure resulting from the Mg-rich composition of the material, but forms a stable interface. Although TiO has a natural tendency to oxidize to non-conductive TiO2, for the purposes of this disclosure, it is desirable to obtain and maintain TiO in a conductive phase rather than obtaining insulating TiO2.

[0044] Helpfully, it has been determined that the TiO / MgO interface is more stable than the TiO2 / MgO interface. The reason why the TiO2 / MgO interface is less stable may be due to the fact that TiO2 does not have a cubic crystal structure like MgO. In contrast, TiO2 can have five different structures, most commonly appearing in the form of anatase or rutile. Anatase is a polymorph of TiO2, forming different and unique crystals. Similarly, rutile is another polymorph of TiO2, and is the most common natural form of TiO2. Both of these do not have a cubic crystal structure like MgO. As a result, the TiO2 / MgO interface has a mismatched structure, which may make its stability less than that of the TiO / MgO interface with matching cubic crystal structure characteristics.

[0045] In addition, the interfacial energy between TiO / MgO is negative, indicating stability, while the interfacial energy between TiO2 / TiO is +3.2 J / m 2 The interface energy between TiO and MgO can be calculated using first-principles density functional theory (DFT) calculations. The interface energy between TiO / MgO is -1.23 J / m 2 The interfacial energy is calculated using formula (III):

[0046] E int = [ E 0,total – n ( E 0,MgO + E 0,TiO )] / (2 A ) (III),

[0047] in E 0,total , E 0,MgO and E 0,TiO is the DFT calculated energy of the interface structure MgO and TiO (confined in the MgO lattice parameters), n is the number of formula units in the interface structure, and A is the area of ​​the interface.

[0048] The negative interfacial energy indicates that the MgO and TiO interface is energetically favorable to form spontaneously throughout the matrix, resulting in ordered planes of MgO and TiO. In other words, the specific ordered arrangement of TiO and MgO is more energetically stable than the TiO+MgO phase separation discussed below. In addition, due to the much larger interfacial energy between TiO and TiO2, the Ti x Mg 1-xO materials can substantially resist oxidation from the TiO cubic crystal structure to the TiO2 phase.

[0049] The amount of higher Ti may improve the overall conductivity of this material, but at the same time, the stability of this material may reduce.Being higher than about 3 or larger atom % Ti at ambient temperature, or being in or higher than about 10 atom % Ti concentration at elevated temperature, at least a portion of this material may be weakly phase-separated into nano domains, forming different nano domains.Supporting weak phase separation into the system of nano domains Ti concentration can be greater than about 3 atom % at ambient temperature, or greater than about 10 atom % at elevated temperature, and lower than about 15,20,25,30,33,35,38,40 atom % Ti.This material can comprise one or more TiO nano domains that keep conducting and keep the MgO nano domains of electrical insulation thus.The radius of each nano domain can be measured as about 1 to 100 nm, 10 to 80 nm or 20 to 60 nm.

[0050] Alternatively, at least a portion of the TiO may form a solid solution with the MgO at a Ti concentration of about 3 or more atomic % at ambient temperature, or at or above about 10 atomic % at elevated temperature. A solid solution is a solid mixture containing a low concentration component uniformly distributed within the crystal lattice of a high concentration component. The solid solution may thus include TiO uniformly distributed within the crystal structure of the MgO.

[0051] At Ti concentrations greater than about 25, 30, or 33.3 atomic %, particularly where exposure to oxygen results in oxidation of at least a portion of the TiO domains, the TiO domains may be formed. x Mg 1-x O system to form one or more ordered Mg-Ti-O compounds, rather than solid solutions or nanodomains. At least a portion of the ordered Mg-Ti-O compounds may be conductive. Table 1 discloses non-limiting examples of ordered Mg-Ti-O compounds, the calculated formation energy of the compounds, whether the compounds are Mg-rich, and the band gap. The ordered Mg-Ti-O compounds are further compared with MgO, TiO, and TiO2 in Table 1 below.

[0052] Table 1 – Non-limiting examples of ordered Mg-Ti-O compounds and their properties compared to MgO, TiO and TiO2

[0053] Compound DFT formation energy [eV / atom] Equivalent composition TiO / (TiO+MgO)[%] Bandgap [eV] <![CDATA[Mg2Ti7O 15 ]]> -3.314 <![CDATA[2MgO – 7TiO – 3O2]]> 77.8 0.0 <![CDATA[Mg2TiO4]]> -3.164 <![CDATA[2MgO – TiO – 1 / 2O2]]> 33.3 3.4 <![CDATA[Mg3Ti9O 20 ]]> -3.317 <![CDATA[3MgO – 9TiO – 4O2]]> 75.0 0.0 <![CDATA[Mg5Ti 13 THE 30 ]]> -3.318 <![CDATA[5MgO – 13TiO – 6O2]]> 72.2 0.0 <![CDATA[Mg 11 Of 25 SHE 60 ]]> -3.320 <![CDATA[11MgO – 25TiO - 12O2]]> 69.4 0.03 <![CDATA[MgTi2O5]]> -3.318 <![CDATA[MgO – 2TiO – O2]]> 66.7 2.7 <![CDATA[MgTi5O 10 ]]> -3.304 <![CDATA[MgO – 5TiO – 2O2]]> 83.3 0.0 <![CDATA[MgTiO3]]> -3.255 <![CDATA[MgO – TiO – 1 / 2O2]]> 50.0 3.5 MgO -2.923 MgO 0 4.7 TiO -2.572 TiO 100 0.0 <![CDATA[TiO2]]> -3.396 <![CDATA[TiO – ½ O2]]> 100 2.7

[0054] The material can thus have a mixture of MgO-Ti phases of various structures and morphologies, depending on the concentration of Ti and the preparation conditions, such as the selection of precursor(s), heat treatment, pH, pressure, temperature, etc., or a combination thereof. In general, the material of formula (I) or (II) - if Mg-rich such that the concentration of atomic Ti is less than about 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 atomic % - provides a stable interface of electrically insulating but stable MgO and electrically conductive TiO.

[0055] A value of about 3 to 10 atomic % thus represents a first threshold value. If the Ti concentration is below the first threshold value, the material may mainly contain MgO and TiO with a cubic crystal structure. If the Ti concentration is above the first threshold value, the material may contain TiO and MgO nanodomains or a solid solution of TiO in MgO and MgO and TiO with a cubic crystal structure.

[0056] A value of about 30 to 33 atomic % represents a second threshold value. If the Ti concentration is below the second threshold value, the material may contain TiO and MgO nanodomains, a solid solution of TiO in MgO, and / or MgO and TiO having a cubic crystal structure. If the Ti concentration is above the second threshold value, the material may contain one or more ordered Mg-Ti-O compounds.

[0057] Due to its composition, structure, and morphology, the material can have the following desirable properties: At 80°C, at pH = 3, and in the presence of ~0.1 ppm HF in solution, the corrosion resistance of the overall material can be less than about 1 µA cm -2 , or under the same operating conditions, the corrosion resistance of the overall material can be at least less than about 0.5 to 10, 1 to 8, or 1.5 to 5 µA cm -2 The electrical conductivity of the coating may be greater than about 100 to 150, 110 to 140, or 120 to 130 S cm -1 The conductivity of the coating may be about 0.1 to 100, 1 to 80, or 10 to 50 S cm -1 The interfacial contact resistance between the substrate and the material can be less than about 0.01 Ohm cm 2 The interfacial contact resistance between the substrate and the material may be less than about 0.001 to 0.2, 0.01 to 0.09, or 0.1 to 0.05 Ohm cm 2 .

[0058] Although BPP has been described as a suitable application for the materials of formula (I) and (II) above, the material may also be suitable for other uses. For example, the materials of formula (I), (II) may be used as part of a surface portion of other industrial applications requiring chemically inert conductive materials, such as batteries, photovoltaics, consumer electronics and / or any other application where a conductive and inert oxide would be beneficial. In addition, a surface portion of a suitable device may include a relatively thin film formed from the material, such that the film is transparent. The material may thus be used as a transparent conductive oxide film, which may be used, for example, in photovoltaics. The application of the material is thus not limited to metals, but any substrate requiring chemically inert and conductive properties. The substrate may thus be glass, ceramic, composite material, polymer, etc. Example

[0059] Examples 1-3

[0060] DFT calculations were used to evaluate the performance of different materials proposed for the surface moiety of the BPP in relation to the chemicals present in the PEMFC environment (especially H + and F - ) surface phenomenon. Example 1 represents MgO, Example 2 represents TiO, and Example 3 represents TiO2. + and F - The single atom adsorption of H3O is used to represent the main H3O in the fuel cell environment. + and the chemical molecule of HF.

[0061] Table 2 shows the H + and F - DFT calculated adsorption energies on cubic crystalline MgO and TiO structures. For reference, the DFT adsorption energies of anatase TiO2 and Cr2O3 are also provided in Table 2.

[0062] Table 2 - H + and F - Adsorption energies on cubic MgO and TiO structures and TiO2 and Cr2O3

[0063] surface H adsorption DFT energy [eV] F adsorption DFT energy [eV] Experimental conductivity [S / m] Rock Salt – MgO +1.965 +0.460 <![CDATA[O(10 -8 )]]> Rock Salt – TiO +0.763 -2.155 <![CDATA[O(10 4 )]]> <![CDATA[Anatase – TiO2]]> +0.039 -1.410 <![CDATA[O(10 -10 )]]> <![CDATA[Cr2O3]]> +0.595 -4.279 <![CDATA[O(10 -4 )]]>

[0064] It can be observed from Table 2 that MgO is the most corrosion resistant species in the test group, as evidenced by the relatively large adsorption energy of MgO. TiO and TiO2 also have reasonable resistance, especially in acidic environments (exposure to F anions). However, only TiO is conductive.

[0065] Embodiment 4-8

[0066] DFT was used to evaluate the conductivity of Examples 4-8. The DFT-calculated electronic density of states (DOS) was evaluated for the MgO-TiO system, specifically, Example 4: TiO, Example 5: MgO, Example 6: Mg 0.97 Ti 0.3 O, Example 7: Mg 0.94 Ti 0.06 O, and Example 8: Mg 0.875 Ti 0.125 O. Figures 3A-3E The evaluation results are shown. Figures 3A-3E The zero on the x-axis is set at the Fermi level (E F ) indicates whether the specific embodiment material is conductive or insulating. Figure 3A It can be observed that Example 4 occupies E F , which indicates metallic state and conductivity. In contrast, Figure 3B Example 5 in shows unoccupied E F In fact, in Figure 3B A large band gap between the unoccupied and occupied states can be seen in Example 5 (MgO) is an electrical insulator.

[0067] Examples 6-8 (whose DOS is depicted in Figure 3C -E) respectively occupy E F , which indicates that Mg x Ti 1-x The conductivity of various compositions in the O system.

[0068] In addition, various methods of synthesizing corrosion resistant and conductive materials are disclosed herein. In at least one embodiment, a method may include forming Ti at a temperature greater than about 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or more. x Mg 1-x Intermetallic alloy. The alloy can be formed by physical vapor deposition, chemical vapor deposition, evaporation, sputtering, electrochemical deposition, etc. The method can further include oxidizing Ti x Mg 1-x Intermetallic alloys. The oxidation may be carried out in a substantially or predominantly oxygen-free environment to inhibit oxidation of TiO to TiO2. A substantially oxygen-free environment is one in which the amount of oxygen is insufficient to induce oxidation of TiO to TiO2. The environment may be completely oxygen-free.

[0069] To control the degree of oxidation of the alloy, one or more oxidizing and / or reducing agents may be added. Non-limiting examples of such agents may be gas species such as Ar, N2, ambient air, or O2, and mixtures of gases, which may be supplied to the furnace where oxidation occurs. Alternatively or in addition to the agent(s), the temperature in the furnace may be varied. For example, a higher temperature may induce more reducing conditions. x Mg 1-x Intermetallic alloys can produce Ti x Mg 1-x O y A material wherein x is a number from 0 to ≤1, and y is a number from 1 to ≤2.

[0070] An alternative method for synthesizing the materials disclosed herein may include doping or replacing MgO powder with a Ti-containing chemical precursor such as TiCl 2. A secondary heat treatment may be performed after the substitution with an inert gas such as N 2 , Ar, etc., which may produce the desired degree of oxidation.

[0071] Regarding doping, it was found that only relatively small amounts of Ti could be doped or substituted into MgO and vice versa. DFT calculations were used to generate the convex hull plot of MgO-TiO, which is plotted in Figure 4 In which various Ti x Mg 1-x O The formation energy of mixtures and their miscibility. Figure 4 As can be seen in the graph, there is a miscibility gap between MgO and the TiO bulk structure, indicating the low doping capacity of TiO relative to MgO. For the purposes of this application, it is undesirable to form electrically insulating TiO2, as the goal is to have TiO in the material. Therefore, for Mg x Ti 1-x O, the calculation takes into account Figure 4 The Mg-rich region of the phase diagram, i.e., x = 0.75, 0.88, 0.94, and 0.97, has packing distances of 150, 85, 36, and 22 meV / atom, respectively. The results indicate that only about less than 3 atom % Ti can be doped into MgO at ambient temperature. This atom % corresponds to ~25 meV / atom. DFT further suggests that at higher temperatures (assisted by secondary heat treatment), it may be feasible for TiO to replace up to 10 atom % of MgO. At concentrations above 3 atom % or 10 atom %, respectively, TiO and MgO may form a solid solution or undergo weak phase separation with distinct nanodomains.

[0072] Another alternative method of preparing the material of formula (I), (II) may include synthesizing the material by atomic layer deposition, wherein the final film has a Ti:Mg ratio of less than 1 / 2, wherein TiO xDeposition on Mg and / or MgO may be at various temperatures of about 100 to 250° C., 120 to 220° C., or 150 to 200° C. The method may include using a precursor such as tetrakis(dimethylamino)titanium, followed by optional annealing at elevated temperature.

[0073] Alternatively, the method for preparing the material of formula (I) or (II) may include preparing the material by physical vapor deposition, chemical vapor deposition, evaporation, sputtering, etc. The material may have a Ti:Mg ratio of less than 1 / 2, wherein MgO x and TiO y co-deposited from stoichiometric targets in appropriate ratios, or where MgO x and TiO y Deposition in reactive oxygen environments.

[0074] Although exemplary embodiments are described above, it is not intended that these embodiments describe all possible forms of the present invention. On the contrary, the words used in the specification are descriptive rather than restrictive words, and it is to be understood that various changes can be made without departing from the spirit and scope of the present invention. In addition, the features of the various embodiments can be combined to form other embodiments of the present invention.

Claims

1. Anti-corrosion and conductive substrate, comprising: The main body part; and A surface portion comprising a magnesium titanium material having formula (I): Of x Mg 1-x SHE y (I), Where x is a number >0 to <1, and y is a number 1 to ≤2, The magnesium-titanium material comprises a conductive TiO phase and an electrically insulating MgO phase, and wherein at least 50% of the magnesium-titanium material comprises MgO and TiO having a cubic crystal structure, and wherein the magnesium-titanium material is configured to impart corrosion protection and electrical conductivity properties to the substrate, The magnesium-titanium material comprises MgO and TiO nanodomains.

2. The corrosion resistant and conductive substrate of claim 1, wherein the magnesium titanium material comprises greater than 10 atomic % Ti, such that the magnesium titanium material further comprises MgO and TiO nanodomains.

3. The corrosion resistant and conductive substrate of claim 2, wherein the TiO nanodomains are conductive.

4. The corrosion-resistant and conductive substrate of claim 1, wherein the electrical conductivity of the magnesium-titanium material is greater than 100 S cm -1 .

5. The corrosion-resistant and conductive substrate according to claim 1, wherein the interface contact resistance between the body portion and the magnesium-titanium material is less than 0.1 Ohm cm 2 .

6. The corrosion resistant and electrically conductive substrate of claim 1, wherein the body portion is steel.

7. The corrosion resistant and conductive substrate of claim 1, wherein the body portion is glass, and the magnesium titanium material is configured to form a transparent film on the surface portion.

8. A bipolar plate for a proton exchange membrane fuel cell, comprising: A metal substrate having a body portion and a surface portion comprising a corrosion resistant conductive material having formula (II): M x HAS 1-x O y (II), wherein M is Ti, A is Mg, x is a number >0 to <1, and y is a number from 1 to ≤2, wherein the corrosion-resistant conductive material has at least 50% of MgO and TiO in a cubic crystal structure, and wherein the corrosion resistance of the surface portion is less than 10 μA cm at 80° C., at a pH of 3, and in the presence of 0.1 ppm HF in the solution -2 , and the electrical conductivity of the surface portion is greater than 100 S cm -1 , The corrosion-resistant conductive material comprises MgO and TiO nanodomains.

9. The bipolar plate of claim 8, wherein the body portion comprises steel.

10. The bipolar plate of claim 8, wherein the radius of each nanodomain measures 1 to 100 nm.

11. The bipolar plate of claim 10, wherein the TiO nanodomains are electrically conductive and the MgO domains are electrically insulating.

12. The bipolar plate of claim 8, wherein the interface contact resistance between the body portion and the corrosion-resistant conductive material is less than 0.1 Ohm cm 2 .

Citation Information

Patent Citations

  • Oxide ceramic

    JP1989093467A